Phenotypic diversity analysis of sweetpotato for breeding dual-purpose varieties. (19th May 2017) - Shumbusha, Damien; Shimelis, Hussein; Laing, Mark; Asiimwe, Theodore
ABSTRACT: The genetic diversity available in sweetpotato has not been explored to develop dual-purpose sweetpotato varieties (DPSVs). The objectives of this study were to assess the level of phenotypic diversity present among sweetpotato varieties grown in Rwanda, and to select suitable parents for breeding DPSVs. Fifty-one diverse sweetpotato genotypes were evaluated in field trials conducted at the Rubona and Karama experimental stations of the Rwanda Agriculture Board using a 6 × 9 unbalanced alpha lattice design with three replications. Genotypes and sites showed significant interaction ( P  < .05), indicating differential response of genotypes in fresh root yield (FRY), root dry matter content, dry root yield (DRY), marketable root number, marketable root weight, flowering frequency and harvest index. The top two genotypes selected for their high FRY were RW11-4923 (20.9 t ha −1 ) and RW11-2419 (20.18 t ha −1 ). RW11-4923 and Wagabolige were the best performers for vine yield, producing 23.67 and 23.45 t ha −1 of vines, respectively. Ukerewe performed well for its DRY (7.09 t ha −1 ), while RW11-4923 had the highest mean dry vine yield (5.17 t ha −1 ). RW11-2910 and 8-1038 had root-to-vine ratios of 2.0 and 1.5, respectively, suggesting their suitability as breeding parents, to breed DPSVs. Two main phenotypic groups with 10 sub-groups were detected through cluster analysis. Principal component analysis showed that the first four components accounted for 76.33% of the phenotypic variation present among the 51 genotypes. The selected sweetpotato genotypes that had a combination of high storage root yields and heavy vine production should be used as parents in developing DPSVs, concurrently incorporating farmer-preferred traits.